PENERAPAN ARSITEKTUR HIGH-TECH PADA PERANCANGAN KONVENSI & EKSHIBISI DI DEPOK - Anthony Sistyo Farhan; Anggraeni Dyah Sulistiowati; Dody Kurniawan (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
Conventions and exhibitions are places to accommodate various types of activities, such as gathering in one place to watch an exhibition of art, goods or certain events to exchange ideas with the aim of increasing insight and knowledge about events held in general.With the design of convention and exhibition buildings in the city of Depok, it is expected to be able to accommodate all activities of the general public related to mass activities. The concept of high-tech architecture is applied to buildings that use renewable materials as well as aesthetic and functional to buildings that can highlight the structure and technology used in the building.